The heterogeneous effect of software patents on expected returns: evidence from India - Eberhardt, Markus; Fafchamps, Marcel; Helmers, Christian; Patnam, Manasa (Elsevier, 2016)
We contribute to the literature on the role of patenting for economic development by analyzing the impact of patent protection for software in India. We find that a proposed broadening of patent eligibility to include software in 2004 had a large positive effect on average returns for listed software companies in India. An unanticipated reversal of this proposed policy change in 2005 resulted in substantial negative returns. We illustrate substantial heterogeneity in the dynamics of these effects across the sequence of events. We also find smaller firms to have been systematically and most significantly affected by the tightening of patent law with regard to software patents.